Male and female soccer players exhibit different knee joint mechanics during pre-planned change of direction - Thomas, C.; dos Santos, T.; Comfort, P.; Jones, P. A. (Sports Biomechanics, 2024)
Change of direction manoeuvres is important in soccer and associated with non-contact anterior cruciate ligament injury, yet it is not known how the mechanics differentiate between males and females during 180° turns. Twenty-eight soccer players (14 males and 14 females) performed 180° turns with ground reaction forces collected over penultimate and final contacts. A two-way (contact - limb) multivariate analysis of variance (MANOVA) were run to examine differences between contact (penultimate and final) or limb (dominant and non-dominant) for sagittal plane hip, knee and ankle peak angles and moments, and frontal plane knee abduction moments and angles between sexes. Average horizontal GRF was increased on the dominant limb, compared to non-dominant and for the final contact compared to the penultimate contact. Knee abduction angles were increased in females compared to males, while the opposite was true for knee abduction moments. Statistically significant differences were evident, with increases in peak vertical GRF, peak hip flexion angle, peak knee flexion angle, peak knee extensor moment, and peak ankle dorsiflexion angle observed in the penultimate contact compared to final contact. The results indicate the penultimate contact during turns helps reduce loading on the final contact, yet male and female soccer players exhibit different knee joint mechanics during pre-planned change of direction.